Sequelas neurológicas após encefalite associada ao herpes vírus simples em crianças : revisão sistemática e meta-análise - Rocha, Natalie Duran (2022)
Introduction: encephalitis is an inflammation of the brain parenchyma manifested by acute symptoms such as fever, headache and other neurological disorders. The etiology, when identified, is most often viral, with herpes simplex virus being a frequent etiologic agent in children. The development of neurological sequelae is a serious outcome associated with this infection. Objective: to evaluate the general prevalence and types of neurological sequelae in children after an acute viral encephalitis caused by HSV. Methods: this systematic review and meta-analysis was developed following PRISMA guidelines. The literature search took place in December 2021 in the MEDLINE (via PubMed), EMBASE, SCIELO, LILACS, COCHRANE, CINAHL, PsycINFO, Web of Science and gray literature databases. Studies were included with children with confirmed HSV infection and which described the neurological sequelae associated with this infection. To calculate the total prevalence and types of neurological sequelae, a random effect model was used. To assess the quality of the studies, we used the National Institute of Health Study Quality Assessment Tools for cohort and cross-sectional studies. To calculate the heterogeneity between the studies used the I² statistic. Results: of the 2827 articles selected in the initial search, 9 studies were included in the systematic review and meta-analysis. The general prevalence of neurological sequelae was 50.7% (95% CI, 39.2 – 62.2). The most frequent sequelae were related to mental disability, with a prevalence of 42.1% (95% CI, 30 – 55.2); on the other hand, the less frequent sequelae were those related to visual impairment with a prevalence of 5.9% (95%CI, 2.2 - 14.6). The included studies were of fair quality and substantial heterogeneity. Conclusion: Neurological sequelae are an important outcome associated with encephalitis caused by HSV in children. Even with the use of antiviral therapy, half of the patients will evolve with some type of disability.